Adobe Illustrator CC learn by video (2014 release) - Chelius, Chad; Safari eBooks ([Place of publication not identified] : Peachpit Press, 2014)
"Experienced instructor Chad Chelius presents 9 hours of high-quality HD video, complete with lesson files, assessment quizzes and review materials. Chad presents a comprehensive introduction to Illustrator, including best practices as well as fundamental illustration and vector artwork concepts. Topics covered include working with styles, paths, and objects, and how to work within the Creative Cloud."--Resource description page.
Title from resource description page (viewed December 18, 2014).
Presenter, Chad Chelius.
Keywords: Adobe Illustrator (Computer file); Computer graphics; Desktop publishing; Electronic books